Meningkatkan Nilai Mutu Pakan Pada Kelompok Ternak Melalui PKM Di Kecamatan Manuju Kabupaten Gowa Propinsi Sulawesi Selatan - Purwanti, Sri; Syahrir, Syahriani; Langkong, Jumriah (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
The purpose of the Community Partnership Program (PKM) program this time were to provided skills to the Tanah Adat and Ngangang Baku livestock groups in Manuju District, Gowa Regency, South Sulawesi Province. The disseminated technology, among others, utilizes bran ammonia as a high protein feed source for poultry, and the manufacture of silage technique feed by utilizing agricultural waste. The Tanah Adat and Ngangang Baku farmer groups are farmers' farmer groups which each member of the farmer group maintains poultry in addition to having large livestock. The problem faced by partners is that the maintenance system is still extensive, the low production is due to the problem of availability of feed with quality that is in line with the needs of livestock, the partners have not been able to utilize local natural resources as feed ingredients. The solutions offered include fulfilling the nutritional needs of livestock by utilizing local resources through the introduction of simple feed processing technology so that farmers can make their own feed and are not dependent on concentrate feed or only use feed without processing. Through this activity, it is expected that farmers and agricultural extension workers will work together to learn to utilize the available local resources into high-yield food. Methods of conducting socialization, training and demonstrations for members of farmer groups as well as mentoring to monitor the development and productivity of post-activity livestock. The results obtained by tabulating the questionnaire given showed that almost all members of the breeders group did not recognize alternative high protein sources and silage techniques. Farmer groups want guidance on an ongoing basis, given the lack of knowledge of breeders and the introduction of technology. Overall the results obtained were very positive responses and active participation from members of the livestock group.